Some Observations on Student Values and Their Implications for Accounting Education: A Comment. - Baker, C. Richard (The Accounting Review, 1974)
Abstract This article presents a comment on the study of some observations on student values and their implications for accounting education in the U.S. If accounting majors are less concerned with wisdom and beauty than other students it may be incumbent upon accounting educators to raise the consciousness level of their students. This could be done by pointing out the scholarly background of accounting and the infinite complexities of designing a useful and reliable method of measuring economic and financial transactions.